2009
DOI: 10.1677/erc-08-0338
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor 1 mRNA is a prognostic factor in ovarian carcinoma: determination by kinetic PCR in formalin-fixed paraffin-embedded tissue

Abstract: Epidemiological and cell culture studies indicate that ovarian carcinoma growth is dependent on estrogen stimulation. However, possibly due to the lack of a reliable biomarker that helps to select patients according to prognostically relevant estrogen receptor (ER) levels, clinical trials using anti-estrogenic therapeutics in ovarian carcinoma have had inconsistent results. Therefore, we tested if ER expression analysis by a quantitative method might be useful in this regard in formalinfixed paraffin-embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Interestingly, pretreatment ESR1 mRNA expression was not related to the response to neoadjuvant chemotherapy. Based on our observation, a validation study was performed on an independent cohort of 114 patients treated with platinum-based adjuvant chemotherapy after surgery for stages I-IV ovarian carcinoma (Darb-Esfahani et al 2009). This study confirmed in a different clinical setting the relevance of ESR1 mRNA expression as a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pretreatment ESR1 mRNA expression was not related to the response to neoadjuvant chemotherapy. Based on our observation, a validation study was performed on an independent cohort of 114 patients treated with platinum-based adjuvant chemotherapy after surgery for stages I-IV ovarian carcinoma (Darb-Esfahani et al 2009). This study confirmed in a different clinical setting the relevance of ESR1 mRNA expression as a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of ESR1 was further validated in formalin-fixed paraffin-embedded tissue samples from an independent population-based cohort of ovarian cancer patients. Data on ESR1 expression from fresh tissue analysis are presented in this article, while data from fixed tissue analysis are presented in the preceding article published in this issue of the journal (Darb-Esfahani et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, in this case the expression should be confirmed by independent methods like RT-PCR or immunhistochemistry to achieve a reliable correlation. Such a fine-tuning -as it has been done for the ESR1 gene in ovarian cancer [22] -must be performed for each gene individually and is therefore not in the scope of present study.…”
Section: Because Gene Expression Arrays Might Be Used To Confirm Er Smentioning
confidence: 99%
“…Although we do not provide a direct comparison between VEGF-C mRNA determinations in fresh frozen and FFPE tissue, our study indicates that formalin-fixed paraffin-embedded tissue is suitable for the determination of VEGF-C gene expression using kinetic RT-PCR. The successful validation of markers identified in fresh frozen tissue after transfer into formalin fixed tissue analysis has recently been published for the prognostic role of estrogen receptor 1 mRNA expression in ovarian cancer [17,18]. To our knowledge, this is the first study to determine VEGF-C expression in epithelial ovarian cancer using kinetic RT-PCR and the first to assess VEGF-C mRNA expression in formalin-fixed paraffin-embedded tissue samples.…”
Section: Discussionmentioning
confidence: 96%